Improving the Knowledge and Skills of Family Welfare Empowerment Members Through Aquaponics Training - Pantiwati, Yuni; Retno Rahadjeng, Erna; Prasetyo, Dony; Novian Indah Sari, Tasya (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
Members of Family Welfare Empowerment (FWE) in Jetis Hamlet, Malang, face challenges related to suboptimal family productivity and limited residential land. This community service initiative aimed to enhance family productivity by training 15 FWE members in aquaponic cultivation and harvest processing. Using intensive mentoring and a learning-by-doing approach, the program was conducted from July to December 2025 and included system installation, the maintenance of catfish (Clarias sp.) and vegetables, and product diversification. Evaluation using pretest and posttest instruments showed a substantial increase in participant capacity. Average knowledge scores increased from 37 to 82, whereas technical skills in system installation and product processing improved from 52 to 81. In addition to cultivation, participants successfully transformed harvested products into value-added products, namely Abon Aquale (catfish floss) and Keripik Viggieponik (vegetable chips). The results demonstrate that aquaponics is a viable urban farming approach for improving food security and economic independence among households with limited land.